Pengaruh Strategi Bersaing dan Inovasi terhadap Kinerja Perusahaan Perhotelan di Sulawesi Utara - Bernhard Tewal (Jurnal Aplikasi Manajemen, 2012)
Various changes have created both opportunities and challenges in the hospitality company’s performance. This study aims to determine competitive strategy and innovation has a significant effect on firm performance. The population is hotel company in North Sulawesi. The samples were tested in 87 companies with Partial Least Square (PLS). The results showed that the competitive strategy and innovation has a significant influence on the performance of hospitality firms in North Sulawesi. This hospitality company has implemented an effective competitive strategy and has undertaken a range of innovative products and process services.Keywords: competitive strategy, innovation, company performance, Partial Least Squre (PLS)